Time-delta method for measuring software development contribution rates - Bishop, Vincil Chapman, III, author; Simske, Steven J., advisor; Vans, Marie, committee member; Malaiya, Yashwant, committee member; Ray, Indrajit, committee member (Colorado State University. Libraries, 2024)
The Time-Delta Method for estimating software development contribution rates provides insight into the efficiency and effectiveness of software developers. It proposes and evaluates a framework for assessing software development contribution and its rate (first derivative) based on Commit Time Delta (CTD) and software complexity metrics. The methodology relies on analyzing historical data from software repositories, employing statistical techniques to infer developer productivity and work patterns. The approach combines existing metrics like Cyclomatic Complexity with novel imputation techniques to estimate unobserved work durations, offering a practical tool for evaluating the engagement of software developers in a production setting. The findings suggest that this method can serve as a reliable estimator of development effort, with potential implications for optimizing software project management and resource allocation.
Keywords: software; contribution rate